Optimalisasi Pembibitan dan Penanaman Sayuran sebagai Strategi Pemberdayaan Perempuan di Desa Midar - Dela Puspita Sari; Ifrohati ,; Vieo Uzmi Zahra; Fiterasiah Al Falah; Viona Violetta; Haris Munandar; Maulana ,; Nazwa , (Universitas Negeri Gorontalo, 2026)
The 84th Routine Community Service (KKN) activity of Group 35 of UIN Raden Fatah Palembang, held in Midar Village, Gelumbang District, Muara Enim Regency, raised the theme of empowering women in strengthening the family economy through the development of pineapple processing and vegetable cultivation businesses. One of the main programs is the utilization of vacant land through seeding and planting vegetables such as chilies, eggplants, and tomatoes. This article aims to examine the seeding and planting process as a strategy for household food security as well as an opportunity to increase income. The approach used was participatory through direct mentoring to village mothers. The results of the activity showed an increase in community awareness about the use of vacant land, improved technical skills in vegetable cultivation, and the opening of household-based economic potential. Seeding and planting are not only understood as agricultural activities, but also as instruments of sustainable social and economic empowerment.